Relationship between Nutritional Status, Frailty, and Cognitive Function among Elderly at Dr. H. Moch. Ansari Saleh General Hospital Banjarmasin - Wiwit Agung Sri Nur Cahyawati; Roselina Panghiyangani; Muhammad Syauqi Abid Muslim; Novia Belinda Rahman (Jurnal Kedokteran Brawijaya, 2022)
The elderly often have nutritional problems. The risk of malnutrition can stimulate the prevalence of frailty and declining cognitive function in the elderly. The study aimed to analyze the relationship between nutritional status, frailty, and cognitive function in the elderly at Dr. H. Moch. Ansari Saleh Hospital Banjarmasin. This study was analytic observational using a cross-sectional method. A sample of 93 elderly was obtained using a total sampling technique according to the inclusion and exclusion criteria. The nutritional status assessment was done using the Mini Nutritional Assessment-Short Form (MNA-SF), the Edmonton Frailty Scale (EFS), and the Mini-Mental State Examination (MMSE). The results showed that the mean of Mini Nutritional Assessment score was 12.00±2.126, the average frailty score was 4.41±1.872, and the average value of cognitive function was 25.98±2.923. Data were analyzed using the Spearman's non-parametric correlation test with a 95% confidence level. The correlation test results between nutritional status and frailty obtained p=0.000 and r=-0.490. The correlation test results between nutritional status and cognitive function obtained p=0.000 and r=0.595. In short, there is a relationship between nutritional status on frailty and cognitive function in the elderly at Dr. H. Moch. Ansari Saleh General Hospital Banjarmasin, it means that the good nutritional status in the elderly, the risk of frailty syndrome will decrease and improve cognitive function.